Bisbenzylisoquinolines as modulators of chloroquine resistance in Plasmodium falciparum and multidrug resistance in tumor cells (1996)
ABSTRACT: Ten naturally occurring bisbenzylisoquinolines (BBIQ) and two dihydro derivatives belonging to five BBIQ subgroups were evaluated in vitro for their ability to inhibit Plasmodium falciparum growth and, in drug combination, to reverse the resistance to chloroquine of strain FcB1. The same alkaloids were also assessed in vitro for their potentiating activity against vinblastine with the multidrug-esistant clone CCRF-CEM/VLB, established from lymphoblastic acute leukemia. Three of the BBIQ tested had 50% inhibitory concentrations of less than 1 mM. The most potent antimalarial agent was cocsoline (50% inhibitory concentration, 0.22 mM). Regarding the chloroquine-potentiating effect, fangchinoline exhibited the highest biological activity whereas the remaining compounds displayed either antagonistic or slight synergistic effects. Against the multidrugresistant cancer cell line, fangchinoline was also by far the most active compound. Although there were clear differences between the activities of tested alkaloids, no relevant structure-activity relationship could be established. Nevertheless, fangchinoline appears to be a new biochemical tool able to help in the comprehension of the mechanism of both chloroquine resistance in P. falciparum and multidrug resistance in tumor cells.